1982
DOI: 10.1002/cne.902070308
|View full text |Cite
|
Sign up to set email alerts
|

Crossed connections of the substantia nigra in the rat

Abstract: The existence of crossed multisynaptic pathways that allow for the interdependent control of activity in one substantia nigra and its contralateral counterpart has been inferred from a number of recent biochemical and neurophysiological investigations. This prompted a reexamination of the connections of the substantia nigra with an emphasis on crossed inputs to and crossed projections from that nucleus. Male albino rats received 20-50-nl pressure injections of a 1% wheat germ agglutinin-conjugated horse-radish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 417 publications
(144 citation statements)
references
References 68 publications
11
130
1
1
Order By: Relevance
“…Contrasting observations were made in the rat VM, revealing notable overlap of cerebellar and nigral territories (Faull and Carman 1968;Di Chiara et al 1979;Herkenham and Nauta 1979;Kultas-Ilinsky et al 1980;Gerfen et al 1982;Deniau et al 1992). Nigral projections dominated this nucleus, whereas cerebellar fibers were found to be thinner and less dense.…”
Section: Va-vl and Vmmentioning
confidence: 69%
See 1 more Smart Citation
“…Contrasting observations were made in the rat VM, revealing notable overlap of cerebellar and nigral territories (Faull and Carman 1968;Di Chiara et al 1979;Herkenham and Nauta 1979;Kultas-Ilinsky et al 1980;Gerfen et al 1982;Deniau et al 1992). Nigral projections dominated this nucleus, whereas cerebellar fibers were found to be thinner and less dense.…”
Section: Va-vl and Vmmentioning
confidence: 69%
“…Such overlapping territories can mainly be assumed in nuclei such as CL and Pf [please note that in rats, a CM is not described; (Faull and Carman 1978;Di Chiara et al 1979;Haroian et al 1981;Gerfen et al 1982;Wiklund and Cuénod 1984;Cornwall and Phillipson 1988;Deniau et al 1992)], in MDpl (Di Chiara et al 1979;Haroian et al 1981;Gerfen et al 1982) and in VM Carman 1968, 1978;Di Chiara et al 1979;Herkenham and Nauta 1979;Kultas-Ilinsky et al 1980;Gerfen et al 1982;Deniau et al 1992). Furthermore, interdigitating projections have been described in VA-VL.…”
Section: Rats Anatomical Evidencementioning
confidence: 99%
“…11). However, several anatomical studies have reported the existence of a descending projection from the SNc to brainstem locomotor networks in mammals (24,25,32,33), and this was further supported by electrophysiological recordings (26). Few authors, however, have considered that this descending projection could originate from meso-diencephalic DA neurons (25).…”
Section: Discussionmentioning
confidence: 93%
“…The second involves behavioral state; the rats in the current experiment were awake and not restrained, whereas the cats in the Nieoullon study wer � anesthetized. Keefe et al (1992) suggests that behaVIOral state may contribute to baseline levels of DA mediated through the corticostriatal projection; perhaps behavioral state also affects stimulation evoked A projection from the PFC also terminates in the sub stantia nigra (Gerfen et al 1982). Excitation of either of t�es .…”
Section: Discussionmentioning
confidence: 99%